The Effect of Rainfall Patterns on the Mechanisms of Shallow Slope Failure - Muhammad Suradi; Andy Fourie (Graduate Program of Syiah Kuala University, 2014)
Abstract - This paper examines how rainfall patterns affect the mechanisms of shallow slope failure. Numerical modelling, utilising the commercial software SVFlux and SVSlope, was carried out for a coupled analysis of rainfall-induced slope seepage and instability, with reference to a shallow landslide took place in Jabiru, Northern Territory (NT) Australia in 2007. Rainfall events were varied in terms of pattern in this analysis. The results revealed that slopes are sensitive to rainfall pattern when the rainfall intensity has a high degree of fluctuation at around the same value as that of saturated hydraulic conductivity. Average rainfall intensity at the beginning of a rainfall period plays a primary role in determining the rate of decrease in initial factor of safety (Fi) towards minimum factor of safety (Fmin). The effect of rainfall events on the slope instability is attributed to the amount of rainwater infiltration into slope associated with rainfall pattern. Keywords: Rainfall pattern; Fluctuating intensity, Shallow failure mechanism; Slope failure; Rainwater infiltration.